The Structure of Small Clusters and IR Spectrum Condensed Matters - G.A. Melnikov; N.M. Ignatenko; V.G. Melnikov; E.N. Cherkasov; O.A. Manzhos (Журнал нано- та електронної фізики)
The article investigates the structure of small clusters, creating an algorithm for calculating the radii of coordination spheres in the structure of such clusters and finding the relationship between the frequencies in the IR spectrum and the characteristics of the most probable cluster in the liquid.